The recovery, readjustment and reintegration programme (R3P): a guide to implementation - Di Lamb; Joanna Jepson; Amos Simms (BMJ Military Health, 2026)
The Recovery, Readjustment and Reintegration Programme (R3P) is a structured, meaning-based psychological support tool that offers peers the opportunity to meet and discuss their shared experiences to enable better coping. Since its inception in 2020, the tool has been adopted nationally by the UK National Health Service and by international military partners. R3P is a leader-led, non-medical initiative, which navigates participants through group discussions focussing on five themes that are acknowledged to cause distress and to linger in a person’s mind long after their occurrence. The five themes, namely morally injurious events, death and suffering, vulnerability, personal and professional challenge, and unrealistic expectations, might be experienced on military deployments but apply equally to everyday life and the occupational environment in the home nation. This paper aims to provide a simple guide of how and when to implement R3P, with considerations for providing a psychologically safe space to optimise fruitful engagement. It will also dispel the myths that have emerged since its inception.